Causes of deficits and ethical dilemmas in scientific research - Walczak-Duraj, Danuta (Annales. Etyka w Życiu Gospodarczym, 2019)
The analysis of the deficits and ethical dilemmas in research will be related to two disciplines of the social sciences: sociology and economics. Research conducted within these disciplines, because of its multi-paradigm nature, tends to be characterized by deficits, not only ethical but also ethical and methodological dilemmas and interpretation reasons. The leading thesis of this paper aims to argue that the looming deficits and ethical dilemmas of Polish researchers in the field of social sciences are two basic but very different premises. The first group of reasons primarily refers to broad ethical deficits, perceived unreliableness in terms of scientific research. It is related mainly to the structural aspects of the functioning of universities and other research units and logic parameterization. In the ethical programs (especially codes of ethics), ethical deficits are identified in three areas of “activity” of research related to the description, diagnosis and interpretation of the results relating to: bragging—e.g. the preparation, recording and publishing of the results that were not obtained; falsification—which means manipulating the research materials, equipment or method, replacing or bypassing the data in such a way that the results are not presented in a true way; plagiarism—the appropriation of other people ideas, methods, results, or terms without proper reference. Plagiarism is also the unauthorized use of information obtained through confidential review of proposals and manuscripts, or e.g. using conference presentations without permission. Its structural evidence is primarily the emphasis on “productivity” and parameterization as the basic criterion, not only of scientific but also academic success-oriented and personalized careers. The second group of reasons refers primarily to broad ethical dilemmas; to the ethical context of social research at every stage of the proceedings: conceptualization, selection of methods, techniques and research tools, conducting research (which concern, for example, the covert participant observation), analysis and interpretation of data, publishing developed and interpreted empirical material. Performing even a cursory analysis of how to present research findings in these two disciplines, you can come to the conclusion that the methodological competence of the investigator does not always go hand in hand with ethical competence. What is more, there is a tendency to downplay the principle that the social sciences should be guided by the principle of the so-called humanistic coefficient.